The impact of trust and service quality on customer loyalty in e-commerce - Malau, Harman; Sitanggang, Juninetenth Keeply F (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This study analyzes the effect of custumer trust and service quality on custumer loyalty through e-commerce custumer satisfaction. This research uses a survey method by distributing questionnaires distributed to Tokopedia, Shopee and Lazada constumers who make transactions in 2024. The object of this research is constumers of Tokopedia, Shopee and Lazada users in North Sumatra. The respondents of the study were taken by purposive sampling obtained 100 respondents. Data is processed using Smart PLS 3. The results of this study show that custumer satisfaction has a significant effect on custumer loyalty, satisfied custumers usually make repeat purchases. Custumers feel comfortable and trust in the company so they will do re-shopping. Satisfied custumers often recommend products to friends and relatives. Loyal custumers have high trust in the company. Custumers believe that the company will continue to provide good service. Custumer trust has no significant effect on custumer loyalty. Custumer trust does not have a significant effect on custumer satisfaction. Service quality does not have a significant effect on custumer loyalty. Product quality and delivery speed often have a greater impact on custumer loyalty compared to service quality. Custumers are more likely to be loyal to platforms that consistently provide quality products and fast delivery. Suggestions for researchers to add custumer behavior variables in digital environments.